Letters Russian nuns from Jerusalem in 1945–1967 - Evgenii V. Palamarenko (Христианство на Ближнем Востоке, 2020)
During the period when the Patriarch of Moscow was Alexy I in the Old City of Jerusalem, which from 1948 to 1967 was under the jurisdiction of Jordan, a group of nuns lived there, consisting of ten people, headed by schema-abbess Eugenia (Mitrofanova), who did not recognize the "schism" Russian Orthodox Church Outside Russia and those who were in spiritual union with the Moscow Patriarchate. After her death in 1959, Princess М.А. Putyatina became her elder sister, who received the name of Seraphim in monasticism, who lived in Jerusalem until 1966. They were practically the only ones who in 1945–1967 informed the Moscow Patriarchate about the state of affairs in Jordan, the Jerusalem Patriarchate and monasteries Russian Orthodox Church Outside Russia. The letters of Schema Abbess Eugenia and Nun Seraphima are valuable documents of that period. The letters have not been published in whole or in part. The aforementioned sisters lived in the Old City of Jerusalem and did not have the right to cross the border with Israel, being direct eyewitnesses to the events in the Jordanian half of Jerusalem at that time. These letters are one of the few surviving testimonies in Russian about church life in Jordanian Jerusalem. The letters served as reports to Moscow and the Moscow Patriarchate about events in the church life of Jordan and Jerusalem. For decades, they represented practically the only source of information from Jerusalem, especially until 1963, when diplomatic relations between the USSR and Jordan were not established. In addition, other monastics who were supporters of the Russian Orthodox Church of the Moscow Patriarchate lived in East Jerusalem. These included several nuns, as well as Hegumen Seraphim (Kuznetsov) and Archimandrite Anatoly (Sakharov). Few of their letters from the period studied were also published.